Uncovering the real outcomes of active renal stone treatment by utilizing non-contrast computer tomography: a systematic review of the current literature - Tokas, Theodoros; Knoll, Thomas (World journal of urology, 2017)
Purpose: To evaluate the stone-free rates (SFRs) and stone clearance rates (SCRs) of extracorporeal shock-wave lithotripsy (SWL), retrograde intrarenal surgery (RIRS), and percutaneous nephrolitholapaxy (PCNL) according to non-contrast computer tomography (NCCT) findings. Methods: Original articles were identified from PubMed. After exclusion of ineligible papers, twenty-three studies with 2494 cases were included in the review. Results: Six SWL, five RIRS and eight PCNL studies were selected. Additionally, four comparative articles were identified. SWL presents SFRs ranging 35-61.3 % and SCRs for residuals <4 mm being 43.2-92.9 %. RIRS studies report SFRs of 34.8-59.7 % and SCRs for residuals <4 mm ranging 48-96.7 %. Finally, PCNL presents SFRs of 20.8-100 % and SCRs for residuals <4 mm being 41.5-91.4 %. According to the comparative studies, SFRs are 17-61.3 % for SWL, 50 % for RIRS, and 95-100 % for PCNL. Conclusions: According to NCCT findings, it seems that PCNL provides better SFRs than ESWL and RIRS. However, further research with comparable and complete preoperative parameters and outcomes could reduce the heterogeneity of current data.